HUMAN RIGHTS CRISIS IN VENEZUELA: A CASE STUDY OF THE CLOSURE OF THE UN OFFICE IN VENEZUELA IN 2024 - Nurman, Syfha Qalbinisa; Sundari, Rio (BHUVANA: Journal of Global Studies, 2025)
This research explores the ongoing human rights crisis in Venezuela, with an emphasis on the closure of the United Nations (UN) Human Rights Office by the Nicolás Maduro regime in 2024. This closure demonstrates the increasing authoritarian nature and resistance to outside scrutiny of increasingly structured human rights violations by the state. Utilizing a descriptive qualitative approach as well as the theory of realism and the concept of national interest, this research examines how the Venezuelan government has implemented a defensive strategy to maintain domestic political control and state independence amid external pressure and sanctions. The findings show that the Venezuelan policy of closing the UN Human Rights Offices exacerbates the sense of impunity for human rights violations, deepens the country’s diplomatic isolation, and worsens the social and economic crisis experienced by the people. This research emphasizes the importance of understanding the dynamics of power politics and national interests to decipher interstate relations and the role of international institutions in the context of complex global pressures.